Bortom kärnfamiljen? Omsorgsgörande från barns perspektiv - Eldén, Sara (Kvinder, Køn & Forskning, 2015)
Research on children and care often take its point of departure in assumptions about the nuclear family as the hub of care. In contrast, this study, by taking its point of departure in the actual practices and relations of care that children experience and engage in – accessed through children’s own narratives of everyday care – suggests new ways of understanding children and care. There is an ‘ordinary complexity of care’ it is argued, apparent in the presence of ‘others’ than parents – e.g., grandparents, siblings, friends, neighbours – doing care in children’s lives. The study also shows how the doing of care still is a gendered activity that seems to extend to female carers outside the nuclear family. Also, children’s own doing of care emerges, a doing that poses critical questions regarding children as ‘competent actors’.